ELECTROCHEMICAL OXIDATION OF ETHANOL USING Ni-Co-PVC COMPOSITE ELECTRODE - Riyanto Riyanto; Mohamed Rozali Othman; Jumat Salimon (Indonesian Journal of Chemistry, 2011)
The morphological characteristics and electrochemical behavior of nickel metal foil (Ni), nickel-polyvinyl chloride (Ni-PVC) and nickel-cobalt-polyvinyl chloride (Ni-Co-PVC) electrodes in alkaline solution has been investigated. The morphological characteristics of the electrode surface were studied using SEM and EDS, while the electrochemical behavior of the electrodes was studied using cyclic voltammetry (CV). It was found that composite electrodes (Ni-PVC and Ni-Co-PVC) have a porous, irregular and rough surface. In situ studies using electrochemical technique using those three electrodes exhibited electrochemical activity for redox system, as well as selectivity in the electrooxidation of ethanol to acetic acid. The studies also found that an electrokinetics and electrocatalytic activity behaviors of the electrodes prepared were Ni metal foil<Ni-PVC2/NiOOH and Co(OH)2/CoOOH catalysts which were determined by the XPS and cyclic voltammetry studies. A better electrokinetics and electrocatalytic activity behaviors electrodes, gave a better results in the electrooxidation of ethanol in alkaline solution.